Comparison of Visceral Fat Accumulation and Metabolome Markers among Cats of Varying BCS and Novel Classification of Feline Obesity and Metabolic Syndrome - Okada, Yuki; Kobayashi, Motoo; Sawamura, Masaki; Arai, Toshiro (Frontiers in Veterinary Science, 2017)
As in humans, obesity and its associated diseases represent the most significant threat to the health of veterinary populations. Previous human studies have provided insights into the risk factors of obesity, complex pathogenesis of obesity-associated diseases, and their life-threatening consequences. In humans, the “metabolic syndrome” represents a cluster of metabolic risk factors associated with the development of cardiovascular disease. Risk factors for metabolic syndrome, such as diabetes, obesity, high blood pressure, and its complications increase healthcare utilization and medical expenses. Early diagnosis and intervention through preemptive approach is in need, and the new International Diabetes Federation definition of metabolic syndrome serves as the universally accepted diagnostic tool that is accessible in clinical settings. In veterinary populations, especially in cats, similar pathophysiological path and disease progression to the development of metabolic syndrome, such as adipokine dysregulations, chronic inflammation, lipotoxicity, are expected. The aim of this manuscript is two-fold. First of all, it presents our preliminary feline obesity study that serves as the basis for discussion of obesity and its metabolic impact on feline population. In this study, we observed the effects of weight gain on energy metabolism using metabolome markers, such as adiponectin and proinflammatory cytokines in correlation with other common biochemical parameters in 14 clinically healthy cats of varying weight status. Further, we evaluated the visceral fat accumulation in 3 subjects of varying Body Condition Scores via CT imaging and laparoscopic examination, and assessed the adipocyte type and size histologically. Mutually antagonizing changes in adiponectin and visceral adipose tissue reflected the pathophysiological derangements leading to metabolic syndrome earlier than the common biochemical predictors such as glucose, liver values, and lipid markers. Secondly, it proposes the novel diagnostic and classification method of feline obesity and metabolic syndrome, based on the established diagnostic criteria of human metabolic syndrome and the presented study results. The results supported our novel “classification of feline obesity” and “Feline metabolic syndrome diagnostic criteria,” suggesting the need to complement adiponectin measurement with visceral adipose tissue volume to better understand the pathogenesis of metabolic disturbances in the feline population.